The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3354/meps11582
|View full text |Cite
|
Sign up to set email alerts
|

Temperature is not a limiting factor for the expansion of Halophila stipulacea throughout the Mediterranean Sea

Abstract: Halophila stipulacea is a Lessepsian migrant that has spread from the Red Sea into the Mediterranean Sea where some authors consider it invasive. It has been suggested that the range of expansion of the species in the Mediterranean will be limited by the 15 ºC sea surface isotherm. Here we tested the effects of temperature on survival, photosynthesis, leaf growth and clonal growth of H. stipulacea. We analysed the temporal and spatial variation of sea surface temperature (SST) in the Mediterranean Sea and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 31 publications
8
55
0
Order By: Relevance
“…Randomly collected fragments of different sizes and lifespans all appeared viable and after tethering the fragments started to grow new roots and leaves within 10 days. Apart from our study, clonal growth rates of H. stipulacea have been reported only once from a mesocosm study in the Mediterranean (Georgiou et al 2016). Reported maximum growth rates are one shoot every two days at the maximum studied temperature of 30°C (Georgiou et al 2016).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Randomly collected fragments of different sizes and lifespans all appeared viable and after tethering the fragments started to grow new roots and leaves within 10 days. Apart from our study, clonal growth rates of H. stipulacea have been reported only once from a mesocosm study in the Mediterranean (Georgiou et al 2016). Reported maximum growth rates are one shoot every two days at the maximum studied temperature of 30°C (Georgiou et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…However, this species can potentially have a large ecological impact at introduced locations due to its extensive range expansion and high tolerance to broad salinity, irradiance and temperature ranges and substrate types (Lipkin 1975;Georgiou et al 2016). These qualities can favour the species in competition with native species and enable it to spread quickly.…”
Section: Introductionmentioning
confidence: 99%
“…(Hillman et al 1995;Bianchi 2007), H. nipponica remained alive by maintaining a high ratio of BGB to AGB when the water temperature was below 15°C along the southern coast of Korea (Kim et al 2012). Similarly, Georgiou et al (2016) demonstrated that Halophila stipulacea, an invasive species in the Mediterranean Sea, ceases clonal growth during winter (at 10°C) but continues to undergo photosynthesis and produces leaf biomass. The average water temperature in the winter (February) increased by approximately 2°C (from 8.4 to 10.1°C) during the past 70 years in southern coastal waters of the Korean peninsula ).…”
Section: Biogeochemical Implications Of the Expansion Of H Nipponicamentioning
confidence: 93%
“…These results imply that sulfate reduction in seagrass sediment is not directly influenced by temperature, but is substantially affected by the amount of DOC exudation from plant roots (Holmer and Nielsen 1997;Kristensen and Alongi 2006), which co-varies with temperature. The clear differences in the optimal growth temperature for the two species further indicated that warming might deteriorate Z. marina growth and that this dominant species might eventually be replaced by H. nipponica in the study area (Pergent et al 2014;Georgiou et al 2016).…”
Section: Control Of Sulfate Reduction At the Two Seagrass Bedsmentioning
confidence: 97%
See 1 more Smart Citation